Parents' Efforts to Foster Virtuous Character Children in Desa Perkebunan Ajamu - Irda Suriani (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2026)
This study aims to describe the efforts of parents in forming commendable morals in children in Ajamu Plantation Village, Dusun XIV, Kebun Meranti Paham, Labuhanbatu Regency. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study show that parents shape children's morals by setting a good example, strengthening religious education, giving advice, and applying educational punishments. Parents also get their children used to carrying out worship and participating in religious activities. In the process of moral formation, parents face obstacles from the surrounding environment because the population in the area is mostly non-Muslim, so there are differences in beliefs and habits that affect children's behavior and associations. This research shows that the role of active and consistent parents is very important in forming commendable morals in children.